Germinal Center Cells Turning to the Dark Side: Neoplasms of B Cells, Follicular Helper T Cells, and Follicular Dendritic Cells - Munguía-Fuentes, Rosario; Maqueda-Alfaro, Raúl Antonio; Chacón-Salinas, Rommel; Flores-Romo, Leopoldo; Yam-Puc, Juan Carlos (Frontiers in Oncology, 2021)
Gaining knowledge of the neoplastic side of the three main cells ̶ B cells, follicular T helper (Tfh) cells and follicular dendritic cells (FDCs) ̶ involved in the germinal centre (GC) reaction can shed light toward further understanding the microuniverse that is the GC, opening the possibility of better treatments. This paper gives a review of the more complex underlying mechanisms involved in the malignant transformations that take place in the GC. Whilst our understanding of the biology of the GC-related B cell lymphomas has increased - this is not reviewed in detail here -, the dark side involving neoplasms of Tfh cells and FDCs are poorly studied, in great part, due to their low incidence. The aggressive behaviour of Tfh lymphomas and the metastatic potential of FDCs sarcomas make them clinically relevant, merit further attention and are the main focus of this review. Tfh cells and FDCs malignancies can often be misdiagnosed. The better understanding of these entities linked to their molecular and genetic characterisation will lead to the prediction of high-risk patients, better diagnosis, prognosis and treatments based on molecular profiles.